PEMETAAN PENGGUNAAN BAHAN AJAR PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 18 SURABAYA - NANIK MUSTA'IDAH (Jurnal Pendidikan Akuntansi (JPAK), 2013)
The study is backgrouded by the low quality of education in Indonesia which is caused by some factors, such as the issue of uncomplitely facilities. It is the teaching material. This study is purposed to know the using of teaching material in eleventh social class SMA Negeri 18 Surabaya and decent of it in the teaching activity. The approach of study is descriptive study with quantity approach. The study instrument are using interview and expert review of sheet questionnaires. The result of expert review is obtained based on scored accounted of likert scale. The result of this study said the teaching material applied in SMA Negeri 18 Surabaya is LKS printing of Kharisma. The result of a teaching material’s expert said that a teaching material in Kharisma LKS has decented to be used in learning teaching process. Keyword : Teaching Material